The Application of Farm Management System in The Grand Parent Stock Farm of PT. Berdikari Unit Lebak - Siti Azizah; Dede Apryliasari; Goh Gerald (Jurnal Manajemen dan Inovasi (MANOVA), 2023)
The research objective was to compare the application of FMS (Farm Management System) and a manual system based on the perception of farm officers at the Grand Parent Stock farm of Berdikari Lebak Unit. This research was conducted from 18 January 2021 to 18 February 2021 at the Grand Parent Stock farm of Berdikari Lebak Unit. Data were obtained by purposive sampling with 30 respondents of Lebak Farm officers, which include the Head of Farm Unit, Farm Officer, and Operators. In addition, data was also obtained from interviews with Berdikari employees in IT Department. This study uses primary data and secondary data. The data analysis was processed using a Likert scale, and the comparison of the application of the FMS and manual systems was used quantitative descriptive analysis. The results showed that the application of the FMS system was better than using the manual system. It can be seen based on the recap time, input time, and data transmission time where the application of the FMS system is faster than the manual system. The manual system data input average is 10 minutes, while the FMS system is one minute. Moreover, the time for sending data is also faster in the FMS system, while in the manual system, it will take 5-10 minutes, depending on the network speed. The implementation of the FMS system results in safer and more reliable data. The application of the FMS system can be integrated with the entire company system, the ERP (Enterprise Resource Planning) system.